Teaching children with autism and related spectrum disorders : an art and a science - Magnusen, Christy (Jessica Kingsley, 2005)
Based on twenty-five years of teaching and working with children who have Autism Spectrum Disorders (ASDs), Christy L. Magnusen contends that it is those teachers who can blend the 'science' of education methodology with the 'art' of teaching who are best able to reach these children. Examining both these aspects of teaching, she takes a fresh look at established and more recent teaching methods such as structuring spaces, emphasising language and planning strategies for transition and generalization, and then explores the art of implementation: why, when and how these techniques should be app.